Perbedaan Pengaruh Latihan Aquatic Dan Land Plyometric Squat Jump Terhadap Tinggi Loncatan Pemain Pemula Bola Voli - , Sugiyanti; , Dwi Kurniawati SST.FT, M.Kes (2016)
Background: Plyometrics is a method to develop eksplosive power. Plyometric exercises performed on grassy surfaces, athletic tracks and the soil surface is called the land plyometric and there are also aquatic plyometric that provides training in the water.The plyometric exercises can improve eksplosive power is an important component in improving the high jump. The high jump in measuring with test that is vertical jump is very important in the game of volleyball to optimize performance when jumping smash. High jump are important which is one important technique in playing volleyball. Objective: Knowing effects of aquatic and land plyometric squat jump training and the effect differences between aquatic and land plyometric squat jump training for height stepping beginner volleyball players. Methods: This research is a quasi experiment with two group pre test and post test design, the sample group I was given aquatic plyometric training and group II was given land plyometric training for 6 weeks with a frequency 2x a week.Measurement of high stepping or vertical jump performed by the vertical jump test. Data analysis using Wilcoxon test to test effects of and effects of of different test using Mann Whitney test. Results: There was an effects of aquatic plyometric squat jump training to jump high beginner volleyball players after the performed statistical tests obtained using Wilcoxon test p-value 0,028. There was an effects of land plyometric squat jump training to jump high beginner volleyball players are the result of p-value of 0,027, and there are differences in the effect after using statistical test Mann Whitney test was obtained p-value of 0,006. Conclusion: There was an differences in the effects of aquatic and land plyometric squat jump training on high jump beginner volleyball players